Math 554 Introduction to Stochastic Processes Instructor: Alex Roitershtein Iowa State University Department of Mathematics Fall 2015 Solutions to Homework #5 2.8 In all the case a is the minimal solution of φ(a) = a in (0, 1]. (b) We have: a = p0 + p1 a + p3 a3 ⇐⇒ 4a3 − 9a + 5 = 0 ⇐⇒ (a − 1)(4a2 + 4a − 5) = 0. √ Hence a = 6−1 . 2 (d) We have: φ(s) = 1−q . 1−qs Hence, α= which implies that α = 1−q ⇐⇒ 1 − q − α + qα2 = 0, 1 − qα 1−q q if q ≥ 1/2 and α = 1 otherwise. 2.9 In general, P(Xn+1 = 0 ∩ Xn 6= 0) P(Xn+1 = 0) − P(Xn = 0) = P(Xn 6= 0) 1 − P(Xn = 0) φ(αn ) − αn αn+1 − αn = . = 1 − αn 1 − αn P(Xn+1 = 0|Xn 6= 0) = (a) We have: P(X2 = 0) − P(X1 = 0) φ(p0 ) − p0 p0 + p1 p0 + p3 p30 − p0 = = 1 − P(X1 = 0) 1 − p0 1 − p0 3 p1 p0 + p3 p 0 = . 1 − p0 P(X2 = 0|X1 6= 0) = (b) We have: φ φ(p0 ) − φ(p0 ) P(X3 = 0) − P(X2 = 0) P(X3 = 0|X2 = 6 0) = = . 1 − P(X2 = 0) 1 − φ(p0 ) Since φ(s) = p0 + p1 s + p3 s3 it is in principle possible to compute it even without calculators. 1 2.11 Let µ := P∞ n=1 npn . Using the notation of the textbook, P(Y1 = 0) = p0 q and P(Y1 = n) = pn q + pn−1 (1 − q), because the parent particle counts if it doesn’t die out. Hence, µ e := E(Y1 ) = ∞ X n pn q + pn−1 (1 − q) = 1 + µ − q. n=1 Therefore, the extinction is certain if q ≥ µ. 2.13 (a) Using the notation of the textbook, q P(Y1 = 1) = P(Y1 = 2) = . 2 P(Y1 = 0) = 1 − q, Hence, µ := E(Y1 ) = q q 3q +2 = . 2 2 2 Therefore, the extinction is certain if q ≤ 2/3. (b) Using the notation of the textbook, we must compute 1 − α(4) = 1 − [α(1)]4 . We have: q q q q α(1) = 1 − q + α(1) + α(2) = 1 − q + α(1) + [α(1)]2 . 2 2 2 2 Therefore (because α(1) is the minimal root), α(1) = and 1 − α(4) = 1 − 16 2(1 − q) , q 1−q 4 . q 2.14 (a) Assume that φ0 (a) ≥ 1. Then, since φ0 (s) is monotone increasing, Z 1 1 − a = φ(1) − φ(a) = φ0 (s)ds > φ0 (a)(1 − a) ≥ 1 − a. a This contradiction establishes the fact that φ0 (a) < 1. (b) Denote ρ := φ0 (a). Using the mean value theorem for derivatives and the fact that αn < α (see p. 56 in the text), α − αn+1 = φ(α) − φ(αn ) ≤ ρ α − αn ). Using induction, α − αn ≤ ρn−1 (α − α0 ) = αρn−1 . 2 (c) Let E := limn→∞ Xn = 0 denote the event of extinction. Then, P(E|Xn 6= 0) = P(E) − P(E ∩ Xn = 0) α − αn α − αn P(E ∩ Xn 6= 0) = = ≤ , P(Xn 6= 0) 1 − P(Xn = 0) 1 − αn 1−α where in the last inequality we used the fact that αn < α (see p. 56 in the text). Thus P(E|Xn 6= 0) ≤ 3 αρn−1 . 1−α